Discontinuous approaches for nonlinear dynamic analyses of an ancient masonry tower. (1st March 2021) - Ferrante, Angela; Loverdos, Dimitri; Clementi, Francesco; Milani, Gabriele; Formisano, Antonio; Lenci, Stefano; Sarhosis, Vasilis
Highlights: Discontinuous approaches to simulate the nonlinear dynamic behaviour of masonry towers. Application of Non-Smooth Contact Dynamics (NSCD) method with LMGC90© code. Application of Discrete Element Method (DEM) with 3DEC© code. Evaluation of the response under repeated accelerograms (seismic sequence) Comparison between coarse and very refined textures. Abstract: The aim of this paper is to present the development of discontinuous approaches to simulate the nonlinear dynamic behaviour of the civic clock tower of Rotella, in the province of Ascoli Piceno (Italy). The study involves the use of the Non-Smooth Contact Dynamics method implemented in the LMGC90© code, where sliding motions are governed by Signorini's impenetrability condition and dry-friction Coulomb's law, and the Discrete Element Method with cohesive and tensional behaviours at the joints in the 3DEC© code. The tower was represented using three different geometric models ranged from the most complex one, including the full geometry and multi-leaf masonry walls, to the simplest one, including the single-leaf walls as a simplification of the real masonry. The numerical results highlighted the modes of failure depending on the shape, size and texture of the masonry and the modalities of progressive damage under dynamic actions. Moreover, both numerical approaches have proven to be capable of simulating large displacements and complete block separations, reproducing complex mechanical behaviours and making predictions on the vulnerability assessment of the historical masonry buildings.